A new tool to assess ecosystem health in large subtropical reservoirs: Development and validation of a Planktonic Index of Biotic Integrity. Issue 1 (2nd January 2019) - Pomari, Juliana; Kane, Douglas D.; Ferreira, Rosa A. R.; Nogueira, Marcos G.
Abstract : We developed and validated a Planktonic Index of Biotic Integrity for subtropical reservoirs to assess their ecosystem health. For this purpose, we analyzed the phytoplankton and zooplankton communities and determined reservoir trophic status in the Paranapanema River system (Southeast Brazil). Eleven dams were constructed in the main course of this river to supply hydropower plants. Three of the reservoirs are accumulation systems (i.e. with high water retention times), whereas the others are run-of-the-river systems. For the study the three larger reservoirs (Jurumirim, Chavantes and Capivara) were selected. Physical, chemical, and biological (phytoplankton and zooplankton) data were obtained in two sampling campaigns carried out in March (wet season) and October (dry season) of 2011. For each reservoir we sampled six stations, arranged on a gradient established between the lotic (Paranapanema River entrance) and lentic (dam) areas. According to the Trophic State Index for tropical/subtropical reservoirs, the sampling stations were categorized between ultraoligotrophic and mesotrophic. Four metrics achieved significant discrimination (out of a set of 20 candidate metrics). The individual metric scores were summed to provide a Planktonic Index of Biotic Integrity score, which ranged as Mesotrophic (4-9), Oligotrophic (10-14) and Ultraoligotrophic (15-20), corresponding to the classification of fair, good and excellent, respectively. Following the longitudinal sequence, Jurumirim was classified as Oligotophic (Good) and both Chavantes and Capivara as Ultraoligotrophic (Excellent). This study demonstrated that the Planktonic Index of Biotic Integrity is a potential tool for monitoring large subtropical reservoirs, as planktonic organisms are sensitive to environmental changes and this index integrates distinct temporal and spatial scales.